Konsep Diri Dan Konformintas Dengan Kecenderungan Gaya Hidup Hedonis Pada Remaja - Nadya Putri Kusherawati; Uswatun Hasanah (Universitas Darul Ulum, 2022)
This study aims to determine whether there is a relationship between self-concept and conformity with the tendency of the Hedonic Lifestyle in Sidoarjo City. This research is a quantitative type. Sampling was done by random sampling. The sample used in this study were teenagers in the city of Sidoarjo, totaling 60 teenagers. The data collection tool used uses the Self-Concept, Conformity and Hedonic scales. Results of Statistical Analysis Correlation Test Spearman's Rho test shows the value of rho x1y: -0.083 with sig. or p : 0.530 (p>0.05), this shows that hypothesis 1 is rejected. This means that there is no correlation between self-concept and hedonism. rho x2y ; 0.316 with sig. or p : 0.014 (p <0.05), this indicates that the 2 hypotheses are accepted, meaning that there is a significant positive correlation between conformity and hedonism behavior. The positive direction means that the higher the peer conformity, the higher the hedonism